A comprehensive review study on composite patch applications - Sen, Murat (Sage Publications Ltd, 2025)
Composite patches (CPs) are used to increase fuel, oil and gas resources efficiency, and improve performance in sectors such as aviation and automotive due to their lightness and durability. These materials strengthen structures thanks to their high strength and contribute to the extension of the life of structures by being used in areas such as marine and construction due to their resistance to corrosion. One of the most important advantages of CPs is that they can be produced in the desired shapes and sizes. This feature provides engineers with flexibility in design and offers ideal solutions for structures with complex geometries. In addition, there is no need for processes such as drilling holes or weakening the existing structure when applying CP. In this way, cracks are prevented from progressing and structural integrity is maintained. This review study presents a thorough investigation of the aspects of the methodology, materials, applications, performance, monitoring and evaluation of CP repairs of composite and metallic structures with investigation of the recent studies on this special area.
Keywords: Bonded patch; composite patch; composite patch performance; patch repair; patch types